Usefulness of BRAF VE1 immunohistochemistry in non-small cell lung cancers: a multi-institutional study by 15 pathologists in Korea - Sunhee Chang; Yoon-La Choi; Hyo Sup Shim; Geon Kook Lee; Seung Yeon Ha; Korean Cardiopulmonary Pathology Study Group (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Background Next-generation sequencing (NGS) is an approved test to select patients for BRAF V600E targeted therapy in Korea. However, the high cost, long turnaround times, and the need for sophisticated equipment and skilled personnel limit the use of NGS in daily practice. Immunohistochemistry (IHC) is a rapid and relatively inexpensive assay available in most laboratories. Therefore, in this study, we evaluate the usefulness of BRAF VE1 IHC in terms of predictive value and interobserver agreement in non-small cell lung cancers (NSCLCs). Methods A total of 30 cases with known BRAF mutation status were selected, including 20 cases of lung adenocarcinomas, six cases of colorectal adenocarcinomas, and four cases of papillary thyroid carcinomas. IHC for BRAF V600E was carried out using the VE1 antibody. Fifteen pathologists independently scored both the staining intensity and the percentage of tumor cell staining on whole slide images. Results In the lung adenocarcinoma subset, interobserver agreement for the percentage of tumor cell staining and staining intensity was good (percentage of tumor cell staining, intraclass correlation coefficient = 0.869; staining intensity, kappa = 0.849). The interobserver agreement for the interpretation using the cutoff of 40% was almost perfect in the entire study group and the lung adenocarcinoma subset (kappa = 0.815). Sensitivity, specificity, positive predictive value, and negative predictive value of BRAF VE1 IHC were 80.0%, 90.0%, 88.9%, and 81.8%, respectively. Conclusions BRAF VE1 IHC could be a screening test for the detection of BRAF V600E mutation in NSCLC. However, further studies are needed to optimize the protocol and to establish and validate interpretation criteria for BRAF VE1 IHC.